2019
DOI: 10.29252/jcmh.6.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder in Preschool Age: Lived Experiences of Mothers

Abstract: Background and Purpose: Mothers are the most important factors in the prognosis of attention deficit hyperactivity disorder in preschool children. Detecting mothers' experiences in daily life increases the potential of improving the effects of interventions on the child and enhancing the parents' level of well being. Therefore, the purpose of the present study was to explore Iranian mothers' experiences in raising preschool children with attention deficit hyperactivity disorder. Method: This research was execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Twelve studies (52.2%) indicated the need for care that goes beyond medication (Cheung et al., 2015 ; Coletti et al., 2012 ; Fridman, Banaschewski, Sikirica, Quintero, & Chen, 2017 ; Hossainzadeh Maleki, Rasoolzadeh Tabatbaei, Mashhadi, & Moharreri, 2018 ; Leitch et al., 2019 ; McIntyre & Hennessy, 2012 ; Nasol, Lindly, Chavez, & Zuckerman, 2019 ; Reale, Frassica, Gollner, & Bonati, 2015 ; Sikirica et al., 2015 ; Simons et al., 2016 ; Sollie & Larsson, 2016 ; Vijverberg, Ferdinand, Beekman, & Van Meijel, 2020 ). Participants reported that medication reduces but does not eliminate ADHD symptoms (Sikirica et al., 2015 ; Simons et al., 2016 ; Sollie & Larsson, 2016 ) and wanted professionals to consider additional therapeutic options (Coletti et al., 2012 ; McIntyre & Hennessy, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies (52.2%) indicated the need for care that goes beyond medication (Cheung et al., 2015 ; Coletti et al., 2012 ; Fridman, Banaschewski, Sikirica, Quintero, & Chen, 2017 ; Hossainzadeh Maleki, Rasoolzadeh Tabatbaei, Mashhadi, & Moharreri, 2018 ; Leitch et al., 2019 ; McIntyre & Hennessy, 2012 ; Nasol, Lindly, Chavez, & Zuckerman, 2019 ; Reale, Frassica, Gollner, & Bonati, 2015 ; Sikirica et al., 2015 ; Simons et al., 2016 ; Sollie & Larsson, 2016 ; Vijverberg, Ferdinand, Beekman, & Van Meijel, 2020 ). Participants reported that medication reduces but does not eliminate ADHD symptoms (Sikirica et al., 2015 ; Simons et al., 2016 ; Sollie & Larsson, 2016 ) and wanted professionals to consider additional therapeutic options (Coletti et al., 2012 ; McIntyre & Hennessy, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants from 17 studies (73.9%) reported the need for ADHD education that improves health literacy for consumers, health professionals, teachers and the broader community (Ahmed, Borst, Yong, & Aslani, 2014 ; Cheung et al., 2015 ; Coletti et al., 2012 ; Fridman et al., 2017 ; Hossainzadeh Maleki et al., 2018 ; Leitch et al., 2019 ; McIntyre & Hennessy, 2012 ; Pahlavanzadeh, Mousavi, & Maghsoudi, 2018 ; Price et al., 2019 ; Reale et al., 2015 ; Rezel‐Potts, Kordowicz, Downs, White, & Prasad, 2021 ; Schrevel, Dedding, van Aken, & Broerse, 2016 ; Sikirica et al., 2015 ; Simons et al., 2016 ; Sleath et al., 2017 ; Vijverberg et al., 2020 ; Walker‐Noack, Corkum, Elik, & Fearon, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations